2008
DOI: 10.1093/icesjms/fsn206
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a genetic cline for Sardina pilchardus along the Northwest African coast

Abstract: Chlaida, M., Laurent, V., Kifani, S., Benazzou, T., Jaziri, H., and Planes, S. 2009. Evidence of a genetic cline for Sardina pilchardus along the Northwest African coast. – ICES Journal of Marine Science, 66: 264–271. In all, 700 Sardina pilchardus from 14 locations throughout the Atlantic and Mediterranean Moroccan coastlines were screened for eight enzymatic loci that show polymorphism. Analysis of allelic frequencies showed a genetic break in the area of the Bay of Agadir, segregating two groups of samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…Tests for correlation between allele frequencies of microsatellite locus Sp22 (4 main alleles, 19 in total) and allozymic locus SOD (2 alleles) in samples collected from the same geographical areas showed that the microsatellite allele Sp22 216 and allozymic allele SOD* 100 (named as in Chlaida et al 2009) exhibited the strongest correlation (R=0.86, P=0.0020) (Fig. 4).…”
Section: P=09306)mentioning
confidence: 97%
See 4 more Smart Citations
“…Tests for correlation between allele frequencies of microsatellite locus Sp22 (4 main alleles, 19 in total) and allozymic locus SOD (2 alleles) in samples collected from the same geographical areas showed that the microsatellite allele Sp22 216 and allozymic allele SOD* 100 (named as in Chlaida et al 2009) exhibited the strongest correlation (R=0.86, P=0.0020) (Fig. 4).…”
Section: P=09306)mentioning
confidence: 97%
“…We do know that such hydrodynamic barrier exists between the Alboran Sea and the Mediterranean (Almeria-Oran front) (Patarnello et al 2007), and the deep ocean separating the Azores and Madeira from the nearby continental shelf probably also acts as a barrier. The abrupt change in allozymic frequency of SOD* off the African Atlantic coast at ~30°N has also been attributed to a hydrodynamic barrier (Chlaida et al 2009), which may also hold for locus Sp22.…”
Section: Genetic Structure Based On Non-neutral Variation and Correlamentioning
confidence: 99%
See 3 more Smart Citations